Revolution from the Inside: Institutions, Legitimation Strategies, and Rhetorical Pathways of Institutional Change. (17th November 2020) - Goddard, Stacie E.
Abstract: Why and under what conditions do a challenger's legitimation strategies shape decisions for institutional reform? I argue that legitimation strategies are critical in defining how institutional defenders evaluate the costs and benefits of institutional reform, and thus in shaping their reaction to a challenger's demands. Legitimation strategies do so through principled persuasion, where defenders come to believe that accepting a challenger's demands will have both material and symbolic benefits, and rhetorical coercion, where defenders accept change out of fear that they will bear costs by undercutting their own legitimacy. Not all challengers effectively legitimate their demands, however. A challenger's capacity to affect change depends on its position within institutions, which gives it the authority to effectively deploy rhetoric. I demonstrate this argument with a brief case of Japan's challenge to the unequal treaty system in the late 19th century. Abstract : China's participation in the international order has increased its ability to challenge the status quo. It is precisely because China became increasingly embedded in institutional resources over time that it has proven capable of legitimating demands for reform: the resources of the WTO, IMF, and UNSC not only constrain, but enable, China's ambitions. China's membership in institutions inside the liberal order has given that state increasing authority to pursue far‐reaching challenges through rhetorical challenges.